Protective effect of oral stem cells extracellular vesicles on cardiomyocytes in hypoxia-reperfusion - Della Rocca, Ylenia; Diomede, Francesca; Konstantinidou, Fanì; Trubiani, Oriana; Soundara Rajan, Thangavelu; Pierdomenico, Sante D.; Gatta, Valentina; Stuppia, Liborio; Marconi, Guya Diletta; Pizzicannella, Jacopo (Frontiers in Cell and Developmental Biology, 2024)
Hypoxia signaling plays an important role in physiological and pathological conditions. Hypoxia in the heart tissue can produce different consequences depending on the duration of exposure to the hypoxic state. While acute hypoxic exposure leads to a reversible acclimatization in heart tissue with normal systemic oxygen supply, chronic hypoxia exacerbates cardiac dysfunction, leads to a destruction of the tissue. Extracellular vesicles (EVs) are small membrane vesicles that act as mediators of intercellular communication. EVs are secreted by different cell types and those produced by oral cavity-derived mesenchymal stem cells (MSCs), including human gingival MSCs (hGMSCs), have pro-angiogenic and anti-inflammatory effects and showed therapeutic role in tissue regeneration. The aim of the present work was to evaluate the potential protective and regenerative role of EVs produced by hGMSCs, in an in vitro model of hypoxia-conditioned HL-1 cardiomyocytes through . Immunofluorescence and Western blot techniques were applied to evaluate the expression analysis of following inflammatory, oxidative stress, angiogenesis, cell survival and apoptotic markers: HIF-1α, P300, NFkB, CCL2, IL1B, IL6, NRF2, CASP-3, BAX and VEGF.. Results showed that hGMSCs-derived EVs exerted protection HL-1 cardiomyocytes exposed to both pre and post hypoxic conditions. Moreover, modulation of CASP3 caspase-3 and BAX expression demonstrated that EVs reduced the apoptosis. The analysis of microRNAs in EVs derived from hGMSCs was performed to assess the epigenetic regulation of the presented markers. The following microRNAs: hsa-miR- 138-5p, hsa-miR-17-5p, hsa-miR-18a-5p, hsa-miR-21-5p, hsa-miR-324-5p, hsa-miR-133a-3p, hsa-miR-150-5p, hsa-miR-199a-5p, hsa-miR-128-3p and hsa-miR-221-3p can directly or indirectly target the studied genes by determining their modulation obtained in our study. The data from this study suggested that EVs obtained from hGMSCs may be considered for the cell free treatment option in hypoxia-driven cardiac tissue dysfunction.